PENGARUH CAPITAL INTENSITY, PROFITABILITAS, DAN SALES GROWTH TERHADAP TAX AVOIDANCE YENI MAR - MAR ATUN SHOLEHA, YENI (Jurnal Akuntansi AKUNESA, 2019)
This research aims to determine the effect of capital intensity, profitability, and sales growth on tax avoidance. The research population is the manufacturing companies that listed on the Indonesia Stock Exchange for the period of 2013-2017. The sampling technique is using a purposive sampling technique. Data analysis technique in this research is multiple linear regression analysis that using SPSS version 23. The results shows that profitability has a positive effect on tax avoidance. These means that the greater the profitability, the greater the companys tax avoidance efforts. While capital intensity and sales growth are not affect tax avoidance. This means that the high and the low of capital intensity and the sales growth are not affect the company in conducting tax avoidance.Keywords: Capital Intensity, Profitability, Sales Growth, Tax Avoidance